الدور الإنساني لوكالة الأمم المتحدة لإغاثة وتشغيل اللاجئين الفلسطينيين UNRWA (1949-2024م) - مصطفى بوشمبة (جامعة محمد بوضياف بالمسيلة, 2025)
تعتبر وكالة الأمم المتحدة لإغاثة وتشغيل اللاجئين الفلسطينيين في الشرق الأدنى (UNRWA) أحد أهم الهيئات الدولية التي ساهم من خلالها المجتمع الدولي في تخفيف الواقع المستجد بسبب الاحتلال الصهيوني لأرض فلسطين، ولعبت دورا كبيرا في هذا الشأن منذ تاريخ إنشائها إلى اليوم. وقد تعرضت هذه الوكالة لعدة ازمات، وانتقادات حالت دون تأديتها لمهامها التي اوجدت من أجلها أول مرة. وهذا البحث تتبع تاريخ إنشاء الوكالة، والهدف منه، كما تعرض بشيء من التفصيل لجهودها الإغاثية والإنسانية التي قامت بها خلال أكثر من سبعين عاما من انطلاقها. وفيه أيضا فقرات وإحصاءات عن هذه الجهود بالأرقام والرسوم البيانية، وتحليل كل ذلك. كما تعرض البحث إلى بعض العراقيل والمعوقات التي حالت دون إتمامها لمهمتها الإنسانية النبيلة، وعلى رأسها الاحتلال الصهيوني الذي هو السبب الرئيسي في ظهور مشكلة اللاجئين وتداعياتها. The United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) is one of the most important international agencies through which the international community has contributed to alleviating the situation created by the Zionist occupation of Palestine. It has played a significant role in this regard since its inception. This agency has faced several crises and criticisms that have prevented it from fulfilling the tasks for which it was first established. This research traces the history of the Agency's establishment and its objectives, and provides some detail on its relief and humanitarian efforts over the past seventy years. It also includes paragraphs and statistics on these efforts, including figures and charts, and an analysis of all of these. The research also addresses some of the obstacles and impediments that have prevented it from fulfilling its noble humanitarian mission, most notably the Zionist occupation, which is the primary cause of the refugee problem and its repercussions.